Learning Management Through the Scaffolding Teaching to Improve Learning Achievement for 1st Year of Secondary Vocational Students - Sun, Jing; Jermtaisong, Rossarin; Lhongsap, Pornpirom (Journal of Roi Kaensarn Academi, 2023)
The objectives of this research were to: 1) compare the 1st year of vocational - secondary students learning achievement on the Fundamentals of Computer Application studying through scaffolding teaching to 70 percent criteria, and 2) compare the pre-and post-learning achievement of the students studying through scaffolding teaching. The research sample was 10, selected by purposive sampling, 1st-year vocational secondary students studying the Fundamentals of Computer Application at Zigong Vocational and Technical School, Sichuan, China, in the academic year 2022. The research instruments consisted of: 1) a learning management plan based on the scaffolding teaching, and 2) a learning achievement test. Mean, percentage, standard deviations, and t-tests were used for data analysis. The research results showed that: 1) the 1st year of vocational - secondary students’ learning achievement on the Fundamentals of Computer Application studying through scaffolding teaching was higher than the 70 percent criteria at the statistical significance level of .05., and 2) the post-learning achievement of the students studying through scaffolding teaching was higher than the pre-learning at the statistical significance level of .05.